Еко-етичките проблеми како круцијален дел на биоетичките дилеми - Донев, Дејан (Аз-Буки, Скопје (Филозофско друштво на Македонија), 2011)
Philosophy always puts a task for itself to conceive the whole reality in relation with totality. In that way until recently, the human was treated like a part of the nature, inweaved in its totality. But from recently, the nature is treated like an object of human superiority. The quick subordination of the nature for the absorbtion and profitable aims became recognizable sign of human act and behavior. Today’s man act robbery upon nature. With its own behavior towards nature, he (the human) deserts himself, because he alienates. It seems like the human mind never stood sincere like this, until now, towards the radical challenges which ask for attention of its own thoughts toward bioethical dillemas . In this sence, how is it possible a salvation of the environment, if that’s not a part of ethical value for all of us? That’s why it’s necessarily a disruption with this traditional position and acceptance of ecological ethics like a priceless value, an ethics which builds esteem for all the beings which are able to feel, including next generations. That’s the most sharp ethics until now, with a general good purpose and rigid responsibility, with an absolute idea of not hurting the others and with an extreme conscious for the universal effects coming from that behavior. Unquestionably it’s necessary to go behind, to call for an integrative opinion. If philosophy’s aim is to keep the conscious for the totality and spreading the notion of loving the great thought and wisdom for successful and good life, ecological ethics is a new contribution towards that philosophy for better human behavior and living for the future.
Eco-ethical Problems as a Crucial Part of Bioethical Dilemmas
Keywords: Bioethics, Eco-Ethics, integrative thinking, rigid responsibility